High Rates of Undiagnosed Psychological Distress Exist in a Referral Population for Spinal Cord Stimulation in the Management of Chronic Pain. Issue 4 (26th November 2015) - Shamji, Mohammed F.; Rodriguez, Jessica; Shcharinsky, Alina; Paul, Darcia
Abstract : Background: Neuropathic pain affects various dimensions of patient health including physical, psychological, and socioeconomic. The spectrum of psychological dysfunction that accompanies this pain phenotype is unknown, as well as differences based on the etiology of the pain among patients referred for spinal cord stimulation (SCS). Methods: We prospectively assessed SCS referral patients with neuropathic pain for features of psychological distress, either mood or anxiety. Demographic data included age, gender, diagnosis, marital status, and educational level. Screening tools were applied for neuropathic pain (Douleur Neuropathic Quatre and Leeds Assessment of Neuropathic Symptoms and Signs) and psychological distress (Beck Depression Inventory [BDI] and Beck Anxiety Inventory [BAI]). Descriptive statistics defined disease prevalence, compared by gender and diagnosis. Logistic regression correlated pain intensity with severity of psychopathology. Results: Among 150 patients with suitable neuropathic pain diagnoses and no treatable structural pathology, 57% were women, median age was 54 years, and 35% and 42% admitted to routine smoking and alcohol use, respectively. The most common diagnoses were complex regional pain syndrome (46%) and failed back surgery syndrome (38%). Depression symptoms were screened positive by BDI in 63% of patients, and anxiety symptoms were screened positive by BAI in 23% of patients. Pain intensity correlated with BDI scores ( p < 0.02) but not BAI scores ( p = 0.43). Conclusion: The high frequency of depressive and anxiety symptoms screened by the Beck scores in this cohort is an order of magnitude higher than seen in the general population. That many of these cases are undiagnosed should motivate clinicians from primary care providers, comprehensive pain specialists, and surgeons to screen SCS patients for such psychopathology. This represents an opportunity to enhance overall pain management as well as success with invasive neuromodulation strategies.